On the methods and applications of digital video transcoding - Liang, Yongqing. (2008)
In this thesis, we mainly investigate the techniques, such as spatially downsizing a compressed video, temporal resolution conversion transcoding used to realize fast forward/reverse playback functions, and variable bit rate transcoding, summarized in the following.